Influence of Age, Gender and Workload Factors Against Work Fatigue on Nurses - Sri Maryuni; Novika Andora (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Work fatigue is a condition that can cause a decrease in vitality and work productivity. The impact of work fatigue can reduce the quality of nurses in providing nursing care. The purpose of this study was to determine the effect of age, gender and workload on work fatigue on nurses at Alimuddin Umar Liwa Hospital, West Lampung Regency. This type of research is a quantitative research with analytic survey and using a cross sectional approach. The population in this study were nurses at the Allimudin Umar Liwa Hospital, West Lampung Regency, amounting to 220 people. The sample in this study amounted to 71 respondents with proportional random sampling technique The workload questionnaire uses a questionnaire that has been made by Nursalam (2016) which consists of 13 questions using a Likert scale. The job fatigue questionnaire used the standard KAUPK2 questionnaire ((Kuesioner Alat Ukur Perasaan Kelelahan Kerja). Data analysis using univariate and bivariate analysis using Chi-squere test. The results showed that most of the respondents were male, amounting to 39 respondents (54.9%), most of the respondents aged > 40 years 37 totaling 52.1%, most of the respondents having a normal workload amounting to 53.3% , and most had 57.7% fatigue. The conclusion of this study is that there is an influence of gender (0.016), age (p-value = 0.014) and workload (p-value = 0.032) on work fatigue in nurses at Allimuddin Umar Liwa Hospital, West Lampung Regency.